A combination of agricultural and energy purposes: Evaluation of a prototype of photovoltaic greenhouse tunnel. (February 2018) - Marucci, Alvaro; Zambon, Ilaria; Colantoni, Andrea; Monarca, Danilo
Abstract: The recent increasing attention in energy production from renewable energy sources has led to photovoltaic (PV) elements, being located on greenhouse roofs. However, their assessment is almost underdeveloped in Italy. The present paper investigated the lack of a spatial database of PV greenhouses in Italy. The first aim is to detect the evolution of PV panels on the roof of greenhouses during several Energy counts (E.C.). The succeeding goal instead aims to examine the shading of PV panels of a prototype greenhouse that enables an environmentally adapting to the intrinsic characteristics. The shading on crops is one of the major limits for the PV installation on the roofs of greenhouses because it causes problems regarding the usual sequence of agricultural activity. Until now many studies applied PV panels as covering material of greenhouses concentrated on flat structures. The present study investigates tunnel greenhouses which, due to their curved shape, do not lend themselves to accommodate easily PV panels on their coverage. The shading variation was analysed inside our prototype greenhouse, by installing PV panels in a checkerboard arrangement. The transparent flexible PV panels, with dimensions of 1.116 m × 0.165 m, are manufactured using mono-crystalline silicon cells, with an efficiency of 18%, incorporated into polymers with high resistance. The difference and distribution of the shading percentage were examined regarding the surface area affected by the PV roof, the total area and the section of the greenhouse. Particularly, variations in the percentage of shading and the size of the shaded area have been observed on the twenty-first day of each month of the year. Results exposed some consistency in the shading percentage, primarily because of the curvilinear shape of the section of the greenhouse. From mid-March to mid-September, the shading was practically and constantly inside the greenhouse during the daytime; while it was partly inside and partly outside the tunnel greenhouse during the remaining months. The percentage of shading with the PV arrangement adopted never exceeds 40% during the year.